2014
DOI: 10.1039/c4sc01290a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gb3 glycosphingolipids differing in their fatty acid chain on the phase behaviour of solid supported membranes: chemical syntheses and impact of Shiga toxin binding

Abstract: The Shiga toxin B subunit (STxB), which is involved in cell membrane attachment and trafficking of Shiga holotoxin, binds specifically to the glycosphingolipid Gb 3. In biological membranes, Gb 3 glycosphingolipids differ in their fatty acid composition and there is strong evidence that the fatty acid alters the binding behaviour of STxB as well as the intracellular routing of the Shiga toxin/Gb 3 complex. To analyse the binding of STxB to different Gb 3 s, we chemically synthesized saturated, unsaturated, a-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
100
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 49 publications
(113 citation statements)
references
References 57 publications
9
100
3
1
Order By: Relevance
“…For lipid bilayers containing DOPC, sphingomyelin, cholesterol and Gb 3 -C24 : 0, which are phase separated at room temperature, no change in the area percentage of the l o phase was observed upon STxB binding experimentally: 13 we have shown that S-Gb 3 tends to remain phase separated in such a DOPC bilayer. Thus, SGb 3 is probably already in a phase separated state in the mixed bilayer even before STxB binds.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…For lipid bilayers containing DOPC, sphingomyelin, cholesterol and Gb 3 -C24 : 0, which are phase separated at room temperature, no change in the area percentage of the l o phase was observed upon STxB binding experimentally: 13 we have shown that S-Gb 3 tends to remain phase separated in such a DOPC bilayer. Thus, SGb 3 is probably already in a phase separated state in the mixed bilayer even before STxB binds.…”
mentioning
confidence: 88%
“…Phase behaviour of such a bilayer is strongly inuenced by STxB clustering as well as the saturation levels and length of the Gb 3 fatty acyl chain. 11,13,15 Despite the important cellular roles of Gb 3 and its signicant impact on the physical behaviour of the lipid bilayers, it has not been studied by simulations before. Therefore, we use all-atom MD simulations to investigate a mixed bilayer of DOPC and Gb 3 with two different acyl chain compositions, Gb 3 -22 : 0 (Gb 3 with a saturated acyl chain with 22 carbon atoms) and Gb 3 -22 : 1 (Gb 3 with an unsaturated acyl chain with 22 carbon atoms and a trans-double bound in C 13 -C 14 ).…”
Section: 10-12mentioning
confidence: 99%
“…They observed the existence of several laterally segregated phases, containing regions of hexagonally packed saturated hydrocarbon chains separated by cholesterol and unsaturated hydrocarbon-rich interstitial regions. Watkins [26,27]. Windschiegl et al used GUVs and planar SLBs comprising a lipid mixture of DOPC/cholesterol/Gb3 to study Shiga toxin-induced Gb3 clustering [28].…”
Section: Artificial Membrane Systems: Essential Tools For Studies On mentioning
confidence: 99%
“…This proved that sites I and II lead to high affinity receptor binding. However, site III played a role in scanning additional Gb3 receptor epitopes available for toxin binding [27].…”
Section: Shiga Toxinmentioning
confidence: 99%
“…Using standard carbohydrate protecting group chemistry, 33,34 bare Gb3 was perbenzoylated, followed by anomeric deprotection and trichloroacetimidate formation. 35 In the following glycosylation reaction, globotriaosyl trichloroacetimidate ( Fig. 1(a)) and either 1,2-di-O-hexadecyl-sn-3-glycerol ( Fig.…”
Section: A Synthesis Of Gb3 Glycolipidsmentioning
confidence: 99%